Læreprocesser i et landskab af praksisfællesskaber: - udforskning af sygeplejerskers professionsidentitetsprocesser gennem uddannelse og arbejde - Lehn, Sine; Holen, Mari (Tidsskrift for Professionsstudier, 2023)
The article explores how nurses form their professional identity through orientations in and out of different communities of practice that they encounter during their basic education and first encounters with the labour market. Inspired by Wenger-Trayner and Wenger-Trayner (2015), professional identity is understood as subjective orientations in the landscape of communities of practice that constitute the nursing profession. The analysis is empirically grounded in qualitative, longitudinal studies of a group of nurses who have been ethnographically followed for seven years so far. The analysis shows how nurses’ professional identity in 2023 develops as movements through a landscape of communities of practice. The analysis shows how professional identity is shaped by participation within the individual community of practice, and that this participation involves both engaging and disengaging learning processes.